Utilization of Botulinum Toxin for Musculoskeletal Disorders. Issue 6 (June 2020) - Moore, Clint; Hulsopple, Chad; Boyce, Brett
Abstract : Abstract: Rehabilitation from musculoskeletal injuries is challenging with multiple intrinsic and extrinsic factors influencing athletes, conditions, and length of recovery. Multidisciplinary treatment strategies aim to address pathophysiology, mechanical, and psychosocial factors of injuries. An essential element in the recovery from musculoskeletal injuries is pain control and the return of physiologic function. There have been significant advancements in the understanding of pain and, therefore, new techniques and management strategies are being used. Botulinum neurotoxin (BoNT) has demonstrated valuable biopharmaceutical properties to provide neuromuscular blockade, which, in some cases, can help to return biomechanical and functional physiologic loss. There is developing literature in BoNT's ability to block pain in the treatment of painful musculoskeletal conditions. Critical analysis of the literature is necessary given the paucity of high-quality, evidence-based literature in the treatment of these conditions. This article reviews the utilization of BoNT in chronic exertional compartment syndrome, osteoarthritis, lateral epicondylosis, plantar fasciopathy, and myofascial pain syndrome. Abstract : Rehabilitation from musculoskeletal injuries requires a multidisciplinary approach to address the pathophysiology, mechanical, and psychosocial factors of injuries. An essential factor in an athlete's performance and recovery from injuries is pain control and the return of the physiologic function. Inadequately controlled pain can lead to chronic injuries, multiple recurrences, or permanent disability. Botulinum neurotoxin demonstrates biopharmaceutical properties that not only provide a neuromuscular blockade but also antinociception properties. This article reviews the utilization of Botulinum neurotoxin in common musculoskeletal injuries including chronic exertional compartment syndrome, osteoarthritis, lateral epicondylosis, plantar fasciopathy, and myofascial pain syndrome.